2005
DOI: 10.2337/diacare.28.5.1182
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Intolerance Is Common in Japanese Patients With Acute Coronary Syndrome Who Were Not Previously Diagnosed With Diabetes

Abstract: OBJECTIVE -Postprandial hyperglycemia has emerged as a new glycometabolic condition associated with an excessive risk for coronary artery disease. We therefore attempted to evaluate the frequency of postchallenge hyperglycemia in patients with acute coronary syndrome (ACS) who were not previously diagnosed to have diabetes and did not have a fasting glucose concentration of Ն7 mmol/l or an HbA 1c level Ͼ6.0%. We further correlated the presence of postchallenge hyperglycemia with the extent of coronary atherosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
42
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 22 publications
8
42
2
Order By: Relevance
“…Both the relative risk for coronary disease and the progressive increase in incidence that appeared to approach 30% after 8 years indicate that modest increases in blood glucose are associated with an increased incidence of CAD. These results extend previous descriptions of the association between elevated glucose and CAD (4,8,15,16) and confirm that commonly used morning glucose determinations can provide a significant indication of CAD risk.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Both the relative risk for coronary disease and the progressive increase in incidence that appeared to approach 30% after 8 years indicate that modest increases in blood glucose are associated with an increased incidence of CAD. These results extend previous descriptions of the association between elevated glucose and CAD (4,8,15,16) and confirm that commonly used morning glucose determinations can provide a significant indication of CAD risk.…”
Section: Discussionsupporting
confidence: 79%
“…Pathologic consequences from modest elevations of glucose are plausible since impaired glucose tolerance and impaired fasting glucose have been associated with macrovascular disease (6) and greater mortality (7). Patients presenting with acute coronary syndrome frequently have glucose intolerance (8), and it has been reported that glucose intolerance but not impaired fasting glucose may be associated with CAD (5,9). In contrast, meta-analysis indicates that glucose above a threshold of 100 mg/dl may also be a significant risk (10).…”
mentioning
confidence: 94%
“…Therefore, we wanted to further investigate the pathogenesis of AGT by estimating beta cell function in this specific patient group. Although disturbed glucose regulation is a common characteristic of patients with AMI, specific attention has not, until very recently [19], been devoted to beta cell dysfunction in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, cross-sectional studies have found only 35-54% of IHD patients have normal glucose tolerance (NGT) [5][6][7][8][9][10][11]. Increased physical activity, healthy food choices and decreased waist circumference may help to lower the rate of progression from IGT to diabetes [12][13][14].…”
Section: Introductionmentioning
confidence: 99%